Demographic, clinical, treatment, outcome, and comorbidities of patients with relapsing polychondritis: experience from Brazilian tertiary center, and literature review - Patricia Pilar Lury Ortale Ueda; Luiz Antonio Leandrini Komati; Samuel Katsuyuki Shinjo (Advances in Rheumatology)
Abstract Background Due to the rarity of relapsing polychondritis (RP), we described the demographic, clinical, treatment, outcomes, and comorbidities of patients with RP from our tertiary service. Additionally, a literature review was conducted. Methods A total of 47 Brazilian patients with RP between 2000 and 2024 were analyzed. All patient data were collected from pre-parametrized and pre-standardized electronic medical records. A literature review using PubMed with “relapsing polychondritis” as the search term included 25 articles after applying the strict exclusion criteria. Results A total of 47 patients were evaluated. The median age was 40 (34–51) years, with a female-to-male ratio of 1.4:1, and 89.4% were of white ethnicity. The median time from symptom onset to diagnosis was 39 months and the median follow-up duration was 7 years. Ear cartilage biopsy was performed in 12.8% of cases. The clinical manifestations included auricular chondritis, arthralgia, and ocular involvement. Approximately half of the patients had hypertension and dyslipidemia, one-third had diabetes mellitus, and one-fifth had hypothyroidism. Tracheostomy and cochlear implantation were required in 12.8% and 6.4% of the patients, respectively. Disease outcomes showed that 46.8% of patients were in remission, 29.8% had active disease, and 25.5% were controlled with immunosuppressive therapy. Mortality occurred in 6.4% of the cases. In the literature review, 25 studies were analyzed, most of which originated in Asia. Studies have reported the classical manifestations of RP, such as auricular chondritis, arthritis, and ocular involvement. The median age of the patients with RP was similar across studies, averaging 46.4 years, with a predominance of female patients. A comparison with the literature showed consistency in clinical manifestations, particularly auricular chondritis and septum nasal chondritis, although few studies have explored comorbidities, disease evolution, and outcomes. Conclusions The reviewed articles described classical clinical manifestations, but few articles reported data on other manifestations and comorbidities that can occur in RP. Our study provided new insights by mapping symptom evaluations, thereby enhancing the understanding of disease evolution. Understanding and characterizing RP will allow for better assistance in its diagnosis and follow-up.